2008
DOI: 10.15288/jsad.2008.69.629
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Stressors, Psychopathology, and Young Adult Substance Dependence: A Prospective Study

Abstract: ABSTRACT. Objective: There is much theory, but sparse empirical evidence, supporting the notion that internalizing symptoms and negative affect are the mechanism by which exposure to stressful life events infl uence the development of substance-use disorders in adolescence and young adulthood. However, many empirical studies have shown that, in addition to elevations in internalizing symptoms, exposure to stressful life events also produces elevations in externalizing behaviors and conduct problems, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 65 publications
(83 reference statements)
0
56
0
Order By: Relevance
“…The four LRB and four SOTA videos were didactic lectures by the fi rst author and incorporated motivational interviewing techniques. Videos gave feedback on participants' beliefs about social norms, risks of consuming more than three drinks per occasion, accurate expectations of alcohol's effects, how to identify and cope with stress, and related topics by asking viewers to write down answers to questions early in the videos and later presenting the optimal answer (Borsari & Carey, 2003;King & Chassin, 2008;Neighbors et al, 2007). The videos also addressed ways to decrease drinking, discussed how to refuse drinks, emphasized a person's ability to change, and helped viewers set realistic goals for altering drinking behaviors (Borsari & Carey, 2001, 2003Carey et al, 2007;Larimer & Cronce, 2007).…”
Section: Interventions and Outcome Measuresmentioning
confidence: 99%
“…The four LRB and four SOTA videos were didactic lectures by the fi rst author and incorporated motivational interviewing techniques. Videos gave feedback on participants' beliefs about social norms, risks of consuming more than three drinks per occasion, accurate expectations of alcohol's effects, how to identify and cope with stress, and related topics by asking viewers to write down answers to questions early in the videos and later presenting the optimal answer (Borsari & Carey, 2003;King & Chassin, 2008;Neighbors et al, 2007). The videos also addressed ways to decrease drinking, discussed how to refuse drinks, emphasized a person's ability to change, and helped viewers set realistic goals for altering drinking behaviors (Borsari & Carey, 2001, 2003Carey et al, 2007;Larimer & Cronce, 2007).…”
Section: Interventions and Outcome Measuresmentioning
confidence: 99%
“…These include externalizing attributes of impulsivity, sensation seeking, and disinhibition (Bates and Labouvie, 1997;Colder and Chassin, 1999;Colder et al, 2002;Li et al, 2001;Mason and Spoth, 2012;Schuckit et al, 2008a;Slutske et al, 1998), and internalizing characteristics of mood and anxiety-related symptoms (Bates and Labouvie, 1997;King and Chassin, 2008). Another key intermediate phenotype is how a person reacts to alcohol (Newlin and Renton, 2010;Quinn and Fromme, 2011), including a low level of response (low LR) to alcohol that refl ects the need for higher blood alcohol concentrations for effects.…”
mentioning
confidence: 99%
“…Whether measured as the response at a specifi c blood alcohol concentration or through the number of drinks needed for effects (Schuckit et al, , 2012b, the low LR is observed before heavy drinking develops and predicts higher consumption per occasion (Chung and Martin, 2009;Quinn and Fromme, 2011;Schuckit et al, 2007aSchuckit et al, , 2008bSchuckit et al, , 2009Schuckit et al, , 2011bVolavka et al, 1996). The impact of a low LR on later heavier drinking is partially mediated by environmental and attitudinal characteristics, including higher peer drinking (Bates and Labouvie, 1997;Schuckit et al, 2011aSchuckit et al, , 2012b, stress and using alcohol to cope (Ellickson et al, 2001;King and Chassin, 2008;Moberg and Curtin, 2009), and positive expectations of alcohol's effects (Agrawal et al, 2008;Pabst et al, 2010).…”
mentioning
confidence: 99%
“…Any relationship between MDEs and AUDs may also stand out to researchers and clinicians because the coexistence of these two conditions may contribute to relapses for both disorders and may make the treatment of the mood condition and the alcoholrelated problems more challenging (Crum et al, 2005(Crum et al, , 2008Hasin et al, 1996;Schuckit, 2006). Also, alcohol itself can produce temporary negative mood swings (not necessarily independent MDEs), especially when consumed in high doses (Birnbaum et al, 1983;Howland et al, 2010;Isbell et al, 1955;Tamerin and Mendelson, 1969), in part by increasing life stresses associated with alcohol problems, causing elevations in stress hormones, and activating brain regions related to stress and negative moods (Childs et al, 2011;King and Chassin, 2008;Sommer et al, 2008). Such effects might be particularly important in individuals predisposed toward major depression, in whom heavy drinking could facilitate the expression of those depressive syndromes (Caspi et al, 2010;Kahler et al, 2002;Wu et al, 2008).…”
mentioning
confidence: 99%
“…It has been hypothesized that depressed individuals might use alcohol to reduce tension and stress, perhaps through learning to imbibe alcohol as a way of coping after observing similar behaviors among relatives and peers (Crum et al, 2008;Henry et al, 2005;Palfai et al, 2007;Schuckit et al, 2009). Early life depressive episodes might also interfere with educational achievement and job performance, potentially producing stresses associated with lower incomes and fewer social supports, with a resulting heavier use of alcohol to cope with life problems (Childs et al, 2011;King and Chassin, 2008). Some support for the role of MDEs as precursors of later alcohol disorders comes from follow-up studies of alcohol-related outcomes in individuals with earlier onset major depressions (e.g., Crum et al, 2008).…”
mentioning
confidence: 99%